2021
DOI: 10.1080/03075079.2021.1953335
|View full text |Cite
|
Sign up to set email alerts
|

Synergy effects in learning? The influence of mathematics as a second subject on teacher students’ physics content knowledge

Abstract: This study explores benefits of studying two related subjects, mathematics and physics, in teacher education. German teacher students study two subjects as a major, which allows for investigating how the development of content knowledge in one subject, mathematics, benefits students' content knowledge in the other subject, physics. The sample included teacher students from 12 major teacher education universities in Germany. Each of the N = 104 physics teacher students, whose second subject was mathematics, ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…The high complexity associated with a university degree in mathematics regularly leads to students being overwhelmed and sometimes even dropping out of their studies (Hoyles et al, 2001 ; Neumann et al, 2021a ). For teacher education in particular, studies have reported negative effects of mathematics as a second subject on the development of pre-service teachers' professional competence (even for competence aspects related to the subject studied besides mathematics; e.g., Neumann et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The high complexity associated with a university degree in mathematics regularly leads to students being overwhelmed and sometimes even dropping out of their studies (Hoyles et al, 2001 ; Neumann et al, 2021a ). For teacher education in particular, studies have reported negative effects of mathematics as a second subject on the development of pre-service teachers' professional competence (even for competence aspects related to the subject studied besides mathematics; e.g., Neumann et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Fisika merupakan ilmu sains yang mempresentasikan hasil ekperimen, rumus, perhitungan, grafik dan penjelasan konseptual sebuah fenomena alam (Ornek dkk., 2008). Disamping itu, Fisika banyak menggunakan konsep matematika, bahkan matematika dianggap sebagai bahasa Fisika yang memiliki fungsi eksistensial dalam pemodelan dan penalaran tentang fenomena tersebut (Uhden et al, 2012;Redish & Kuo, 2015;Neumann et al, 2021). Dalam perkembangan selanjutnya, pemanfaatan teknologi dalam bidang Fisika dilakukan sebagai upaya meningkatkan kemampuan belajar peserta didik termasuk kemampuan berpikir matematis atau yang dikenal dengan mathematical thinking skill.…”
Section: Pendahuluanunclassified
“…Disamping itu, Fisika banyak menggunakan konsep matematika, bahkan matematika dianggap sebagai bahasa Fisika yang memiliki fungsi eksistensial dalam pemodelan dan penalaran tentang fenomena tersebut (Uhden et al, 2012;Redish & Kuo, 2015;Neumann et al, 2021). Dalam perkembangan selanjutnya, pemanfaatan teknologi dalam bidang Fisika dilakukan sebagai upaya meningkatkan kemampuan belajar peserta didik termasuk kemampuan berpikir matematis atau yang dikenal dengan mathematical thinking skill.…”
Section: Pendahuluanunclassified